Tetronic® 904-containing polymeric micelles overcome the overexpression of ABCG2 in the blood-brain barrier of rats and boost the penetration of the antiretroviral efavirenz into the central nervous system - Roma, Martín Ignacio (2015)
Aim: To assess the involvement of ABCG2 in the pharmacokinetics of efavirenz in the blood–brain barrier (BBB) and investigate a nanotechnology strategy to overcome its overexpression under a model of chronic oral administration. Materials & methods A model of chronic efavirenz (EFV) administration was established in male Sprague–Dawley rats treated with a daily oral dose over 5 days. Then, different treatments were conducted and drug concentrations in plasma and brain measured. Results: Chronic treatment with oral EFV led to the overexpression of ABCG2 in the BBB that was reverted after a brief washout period. Moreover, gefitinib and the polymeric amphiphile Tetronic® 904 significantly inhibited the activity of the pump and potentiated the accumulation of EFV in CNS. The same effect was observed when the drug was administered within mixed micelles containing TetronicT904 as the main component. Conclusion: Tetronic 904-containing polymeric micelles overcame the overexpression of ABCG2 in the BBB caused by chronic administration of EFV then boosting its penetration into the CNS.